Foliar diagnosis in citrus. II. Effect of cultivars and of leaf collecting quadrants on micronutrient amounts - de Oliveira, Juarez Patricio; de Carvalho, Janice Guedes; Malavolta, Eurípedes; de Paula, Miralda Bueno; de Souza, Maurício; Guilherme, Luiz Roberto Guimarães (Pesquisa Agropecuaria Brasileira, 1994)
The effect of the position of the leaves on the tree, collected for chemical analysis, in relation to the quadrants in four citrus cultivars was studied. The experiment was conducted in commercial orchards at Vitória Farm in Alfenas, MG, Brazil, where the leaves were collected from 'Pera Rio', 'Valência', and 'Baianinha' orange trees and from 'Murcote' mandarin trees, grafted on 'Rangpur' lime rootstock. An experimental design consisting of randomized blocks with four replications was used. The leaf collecting quadrants made up the samples, forming the following treatments: North, South, East, West, North and South, East and West and leaves collected from four quadrants (test plot). With relation to leaf sampling quadrants, only the 'Murcote' mandarin tree presented variations in the B and Zn content, while the 'Pera Rio', 'Valência' and 'Baianinha' cultivars showed no differences in foliar content of the micronutrients analysed (B, Cu, Fe, Mn and Zn), as a result of the foliar sampling quadrants. Comparing the micronutrient content among the cultivars, 'Baianinha' was generally the one that showed the highest amounts, followed by 'Valência', 'Pera Rio' and 'Murcote'.
Keywords: leaf position on the tree; mineral nutrition; 'Pera Rio' orange tree; 'Valência' orange tree; 'Baianinha' orange tree; 'Murcote' mandarin tree